Moral Sensitivity and Science Cognitive Learning Outcomes of Junior High School Students through the Meaningful Learning Model - Fitri Halimatus Syaidha; Septi Budi Sartika; Aprilin Astuti; Najah Baroud (Journal of Natural Science and Integration, 2025)
This study was intended to describe the improvement of students’ moral sensitivity and cognitive learning outcomes through the application of the Meaning Learning Model. The research employed a pre-experimental design with a one-group pretest–posttest approach. The population consisted of 70 seventh-grade students from two classes at SMP Negeri 1 Sidoarjo. A purposive sampling technique was used to select classes with below-average academic performance. Data were collected using pretests and posttests for both moral sensitivity and cognitive learning outcomes. The research instruments consisted of a moral sensitivity test and a cognitive learning outcomes test. Data were analyzed descriptively using the N-Gain formula to determine the improvement levels in moral sensitivity and cognitive learning outcomes. The analysis results showed that students’ moral sensitivity improvement was categorized as medium (39%) and low (61%), while cognitive learning outcomes were classified as high (7%), medium (54%), and low (38%). The overall moral sensitivity level was in the “sensitive” category (46%), and students’ cognitive performance predominantly reached the C4 domain (70%). In conclusion, the Meaning Learning Model contributed to an increase in students’ moral sensitivity within the low category and in cognitive learning outcomes within the medium category. Moreover, students’ moral sensitivity was classified as sensitive, and their cognitive achievements were primarily at the C4 level. Keywords: cognitive learning outcomes, meaningful learning model, moral sensitivity.